Fixed Lingual Retainer Positioner: A narrative review - lakhanam, medha; Srivastava, Kamna; Singh, Raghavendr (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2020)
Retention is one of the most critical phase of Orthodontic treatment . Angle stated that "the problem involved in retention are greater  than the difficulties being encountered in the treatment, and tests the utmost skill of the operator. The various retention appliances available include Removable retainers and bonded retainers. Removable retainers have their own advantages and disadvantages, but they need patient’s compliance to wear them.Fixed retainers consist of a length of orthodontic wire that is bonded on the lingual aspect of tooth .The major advantages of bonded retainers includes invisibility, no patient compliance required and long term retention. Bonding of a lingual retainer is a challenging and technique sensitive procedure because it requires long working time and has a risk of contamination from saliva and moisture, leading to bond failure as it is difficult to adaptation of the retainer wire and further stabilization of contoured retainer wire in the oral cavity during bonding.If retainer wire can be effectively stabilized over the lingual surface of tooth prior to bonding, bonding becomes a simple process.Various methods used to stabilize lingual retainer before bonding  involves use of separators (Kesling and elastomeric separators), materials like resin, memosil, glue etc or use of metal Stablizers in form of W,V or use of wires . The objectives of this article is to compile the different retention techniques used to stabilize the lingual retainer wire for bonding altogether at one place. Keywords: Retainers, lingual aspect, Bonding, Stablization